Tales of the forgotten founders - Allen, C W (Santa Fe, NM : Cinnabar Moth Publishing LLC, 2023)
"Zed and Tuesday ought to be living the good life. After all, it's not every day two kids take down an evil dictator and their mom gets put in charge of an entire dimension. But after moving into Falinnheim's palace, they learn that life as royalty isn't as carefree as they'd imagined. Mysterious hidden passages aren't the only secrets lurking within the palace walls. When the siblings discover a stash of banned books, they realize everything they've been told about Falinnheim's history might be a lie. And though contact between worlds has been cut off for centuries, returning home might not be as impossible as their parents claim. Could the adventures of a runaway monk, a reluctant viking, a silent ambassador, and a rebel librarian hold the solutions to both problems? To find the truth, Tuesday and Zed will have to learn the stories of Falinnheim's forgotten founders"--
Ages 12-16
Grades 10-12